Influence of Hsa on Micellization of Nlss and Bc: An Experimental-Theoretical Approach of Its Binding Characteristics - Sanchez-Poblete, J (Elsevier B.V., 2022)
Blood albumins play a very significant role in several biological operations and act as carriers for the transportation and circulation of various endogenous as well as exogenous materials. Experimental as well as computational studies have been carried out in understanding the major binding properties of the system. This investigation explains the interactions of Human serum albumin (HSA) with N-Lauroyl sarcosine sodium salt (NLSS) and benzethonium chloride (BC), which has been explored by means of conductometric, spectroscopic as well as computational studies. Phenomenon of micellization is hindered in several concentrations of protein (HSA) as well as by temperature. Binding ability of HSA with NLSS and BC has been obtained through UV–visible and fluorescence studies. Computational study revealed the presence of seven binding pockets in HSA, out of which the most stable binding pockets for NLSS and BC includes pocket1 and pocket2. © 2022 Elsevier B.V.